Financial Sector Assessment Program After Ten Years-Experience and Reforms for the Next Decade. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Ten years after its inception, the FSAP has established itself as an important instrument for assessing financial systems around the world. More than three-quarters of the membership have volunteered for FSAP assessments or agreed to do so in the near future, including almost all the G20 countries. Previous reviews have confirmed that the FSAP has helped deepen the understanding of countries' financial sectors and linkages with the rest of the economy, enriched the policy dialogue, and ensured consistency of Bank and the Fund advice, the last being a feature highly valued by participating countries. As also noted in the Malan Report, the collaborative nature of the FSAP adds value by effectively addressing areas of financial sector policy where developmental and stability concerns are interlinked and overlap and by facilitating knowledge spillovers between the two institutions. These past reviews have noted, however, the need to make the FSAP more flexible, responsive, and continuous, to deepen and strengthen the analytical toolkit, and to integrate the FSAP more closely with the Bank's and the Fund's other financial sector work.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet